PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN LKS KREASI SISTEM RESPIRASI TERHADAP HASIL BELAJAR SISWA SMA - Sri Mulyani Endang Susilowati; Abadia Delima; Priyantini Widiyaningrum (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2017)
This study aims to determine the effect of Problem Based Learning (PBL) model aided LKS Creation Respiratory System to student learning outcomes MAN 1 Magelang. This study uses a quasi-experimental design. The sample used is a class XI MIA 6 as control class and XI MIA 5 as experimental class. Sampling technique using cluster random sampling. The results showed that the average cognitive achievement, experimental class is better than the control class, namely 66.97>58.70. Based on data analysis psychomotor learning outcomes, the experimental class get better results than the control class, is 76.67%. On the affective aspects in the experimental group also showed better results is 79.99% while the control group is 62.32% with both good category. Both classes have reached school classical completeness is ≥ 75%. Classical completeness experimental group reached 81.25%, while the control group 75%. The average yield of 91.5% the teacher's performance is very good. In general, teachers and students also respond very well to applied learning. Conclusions from this research is a model of PBL aided the Respiratory System LKS Creation a positive effect on learning outcomes of students of class XI MIA MAN 1 Magelang the academic year 2015/2016.